Imperfect Information, Uncertainty, and Credit Rationing - Jaffee, Dwight M.; Russell, Thomas (Quarterly Journal of Economics, 1976)
I. Introduction, 651.—II. The model of borrowing behavior, 652.—III. Lender and market behavior under competitive conditions, 658.—IV. Market solutions under monopoly, 663.—V. Conclusion, 664.—VI. Appendix, 665.